Partisipasi Masyarakat Dalam Meningkatkan Pemberdayaan Pembinaan Sosial Budaya Masyarakat di Kabupaten Timur (Studi di Dinas Pemberdayaan MAsyarakat dan Desa Kabupaten Kutai Timur) - Rusmawati dan Wesley Liano Hutasoit (Prodi Ilmu Administrasi Negara, 2018)
East Kutai Regency as an integral part in the system of RegionalAutonomy Government has the right, authority and obligation ofautonomous regions to manage and manage their own government affairsand public interests of Samarinda City according to the laws andregulations. Autonomous Region is a legal community unity which hasterritorial boundaries that are authorized to regulate and managegovernment affairs and public interests according to their own initiativebased on community aspirations in the system of the Unitary State of theRepublic of Indonesia.The process of community empowerment is one of the keys to socialwelfare. Community involvement, whether physically, thoughtfully,materially or financially, is expected to increase the sense of community andsense of belonging and process of empowerment to the community. Thusthere is a strong link between empowerment and participation.In community empowerment, community participation or involvementis needed in the implementation of empowerment, community participationbased on self-willingness means that villagers participate in empowermentbased on confidence and awareness that comes from within themselves.Community empowerment can be defined as a process that buildspeople or communities through the development of community capacity,changes in community behavior, and community organizing. From thesedefinitions, there are three main objectives in community empowerment:developing people's capacity, changing people's behavior, and organizingthemselves.The purpose of empowerment in the social and cultural field is torealize the welfare of the people which is characterized by the improvementof the quality of decent and dignified life and to give primary attention to thefulfillment of basic needs. The general targets to be achieved are increasing life expectancy, declining rate of population growth, decreasing total birthrate, decreasing coarse mortality rate, increasing social and culturalresilience, increasing position and role of women, increasing activeparticipation of youth, as well as increasing culture and sportingachievement. To achieve these objectives and targets, various social andcultural empowerment policies and programs have been implemented,covering the areas of health and social welfare, including population andfamily planning; culture; position and role of women.